Analisis Kelayakan Buku Teks Akidah Akhlak Kelas IV Pada Kurikulum Madrasah (KMA 183 Tahun 2019) Untuk Memenuhi Kebutuhan Pembelajaran Abad 21 - Miftah Sabillah; Diah Laila Wulan (Prosiding Seminar Nasional Ilmu Pendidikan Agama dan Filsafat, 2025)
In the 21st century learning era that demands the integration of 4C skills and digital literacy, the textbook Akidah Akhlak Class IV MI based on the 2019 KMA 183 Curriculum needs to be evaluated for its suitability to be relevant in shaping students' Islamic character. This study aims to analyze the suitability of the book's content, presentation, language, and graphics according to BSNP standards, with a focus on the strengths of active learning and the weaknesses of technology integration such as QR codes and science-technology interconnections. The descriptive qualitative method through library research uses the 2020 Kemenag textbook by Subkhiaton Noor as primary data, supported by BSNP instruments and comparisons with other books. The results show that the book is very suitable overall: very good content suitability (accurate material, relevant KI-KD, supports 4C through discussion and reflection), good presentation (systematic structure, HOTS-LOTS, glossary), good language (communicative, appropriate to students' cognition), graphics pass with minor improvements in visual consistency, so it is effective for contextual learning even though it needs additional digital features.